CHALLENGES AND SOLUTIONS FACED BY FITNESS CENTERS IN DEALING THE VUCA ERA - Afifah Salihah; Muhamad Rizal; Tetty Herawaty (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
COVID-19 has had a huge influence on people's lives, and not simply in terms of numbers. Several events have been postponed or cancelled, including political, economic, sporting, educational, and other socio-cultural activities. In the vuca period, the fitness center business industry has also felt the effects of covid 19. Using VUCA Prime, the authors assess the capacities of two fitness centers in Bandung, Indonesia, using a descriptive qualitative technique. On the vuca prime side, both firms have advantages and disadvantages. Although both organizations are prepared to meet the vuca era, both must improve on their respective sides, such as strategy selection, competitive analysis, and the environment outside the system that is of concern to extend the target market. Authors and other papers also suggest about the leader who will lead and be part of the team should have some capabilities like to adapt, to control, be creative, be innovative, be general, and be absorptive. Keywords: VUCA; VUCA Prime; Fitness Center; Covid-19; Gym.